ASSESSMENT FINANCIAL MECHANIZM ACTIVITIES OF ENTERPRISE SUBJECTS - Daniyarov Kuatbay Dauirxanovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article reveals the financial mechanisms of the activities of entrepreneurial subjects. The main criterion for the effective functioning and development of entrepreneurship should be the possibility of a stable and gradual exit from the crisis situation.